Nursing Care for Type 2 Diabetes Mellitus Patients Based on Nola J. Pender's Health Promotion Model: A Case Report - Danur Azissah Roesliana Sofais; Irna Nursanti (GLOBAL HEALTH SCIENCE GROUP, 2026)
Type 2 Diabetes Mellitus (T2DM) is a global health burden with increasing prevalence. Persistent hyperglycemia can lead to both microvascular and macrovascular complications. The patient's adherence to therapy, especially lifestyle modifications (diet and physical activity), is the main determinant of treatment success. The purpose of this case report is to analyze the basic concepts, key components, and application of the Nola J. Pender Health Promotion Model in the nursing practice of Type 2 Diabetes Mellitus. This study employed a descriptive case report design. Data were collected through comprehensive nursing assessment, including patient interviews, physical examinations, anthropometric measurements, laboratory results, and review of medical records. Data analysis was conducted using a theory-based approach by systematically mapping patient data to the components of Nola J. Pender’s Health Promotion Model. The analysis showed that the Health Promotion Model effectively guided nursing interventions to promote positive health behaviors, such as physical activity, balanced nutrition, medication adherence, and stress management. This model provides a comprehensive framework that considers personal, interpersonal, and situational factors in the formation of health behaviors. Nola J. Pender's Health Promotion Model provides systematic guidance for nurses to identify factors influencing health behaviors and design holistic, client-centered interventions.